2018
DOI: 10.1038/s41598-017-18923-5
|View full text |Cite
|
Sign up to set email alerts
|

Flux of the biogenic volatiles isoprene and dimethyl sulfide from an oligotrophic lake

Abstract: Biogenic volatile organic compounds (BVOCs) affect atmospheric chemistry, climate and regional air quality in terrestrial and marine atmospheres. Although isoprene is a major BVOC produced in vascular plants, and marine phototrophs release dimethyl sulfide (DMS), lakes have been widely ignored for their production. Here we demonstrate that oligotrophic Lake Constance, a model for north temperate deep lakes, emits both volatiles to the atmosphere. Depth profiles indicated that highest concentrations of isoprene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 77 publications
9
37
1
Order By: Relevance
“…These events contribute towards shaping a summertime aerosol number size distribution that is characterized by a dominant Aitken mode (particles with diameters between 10 and 100 nm) in this region (Croft et al, 2016a), similar to observations at other pan-Arctic sites (Tunved et al, 2013;Asmi et al, 2016;Nguyen et al, 2016;Freud et al, 2017;Gunsch et al, 2017;Heintzenberg et al, 2017;Kolesar et al, 2017). Summertime Arctic aerosol size distributions are also characterized by a suppressed accumulation mode (particles with diameters between 100 and 1000 nm) due to the efficient wet removal processes in frequently drizzling low clouds (Browse et al, 2014) and the limited transport from lower latitudes (Stohl, 2006;Law and Stohl, 2007;Korhonen et al, 2008).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…These events contribute towards shaping a summertime aerosol number size distribution that is characterized by a dominant Aitken mode (particles with diameters between 10 and 100 nm) in this region (Croft et al, 2016a), similar to observations at other pan-Arctic sites (Tunved et al, 2013;Asmi et al, 2016;Nguyen et al, 2016;Freud et al, 2017;Gunsch et al, 2017;Heintzenberg et al, 2017;Kolesar et al, 2017). Summertime Arctic aerosol size distributions are also characterized by a suppressed accumulation mode (particles with diameters between 100 and 1000 nm) due to the efficient wet removal processes in frequently drizzling low clouds (Browse et al, 2014) and the limited transport from lower latitudes (Stohl, 2006;Law and Stohl, 2007;Korhonen et al, 2008).…”
Section: Introductionsupporting
confidence: 69%
“…Similar to their effects in other regions, aerosols interact directly with incoming solar radiation via scattering and absorption (Charlson et al, 1992;Hegg et al, 1996;Yu et al, 2006;Shindell and Faluvegi, 2009;Yang et al, 2014) and indirectly through the modification of cloud properties by acting as the seeds for cloud droplet formation (Lohmann and Feichter, 2005;McFarquhar et al, 2011). In the summertime Arctic, efficient wet removal by precipitation and the smaller extent of the polar dome limit the transport of pollution from lower latitudes and maintain an atmosphere that is more pristine than in the Arctic winter and springtime (Barrie, 1995;Polissar et al, 2001;Quinn et al, 2002;Stohl, 2006;Garrett et al, 2011;Brock et al, 2011;Fisher et al, 2011;Sharma et al, 2013;Xu et al, 2017;. As a result, natural regional Arctic sources make strong contributions to summertime Arctic aerosol, to the related radiative effects, and to associated uncertainties (Korhonen et al, 2008;Leck and Bigg, 2010;Heintzenberg and Leck, 2012;Karl et al, 2013;Carslaw et al, 2013;Heintzenberg et al, 2015;Croft et al, 2016b;Willis et al, 2016Willis et al, , 2017Burkart et al, 2017a;Mungall et al, 2017;Dall'Osto et al, 2017, 2018aBreider et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%
“…These events contribute towards shaping a summertime aerosol number size distribution that is characterized by a dominant Aitken mode (particles with diameters between 10 and 100 nm) in this region (Croft et al, 2016a), similar to observations at other pan-Arctic sites (Tunved et al, 2013;Asmi et al, 2016;Nguyen et al, 2016;Freud et al, 2017;Gunsch et al, 2017;Heintzenberg et al, 2017;Kolesar et al, 2017). Summertime Arctic aerosol size distributions are also characterized by a suppressed accumulation mode (particles with diameters between 100 and 1000 nm) due to the efficient wet removal processes in frequently drizzling low clouds (Browse et al, 2014) and the limited transport from lower latitudes (Stohl, 2006;Law and Stohl, 2007;Korhonen et al, 2008).…”
Section: Introductionsupporting
confidence: 69%
“…Previous studies also reported fluorescent water-soluble organic aerosols in the High Arctic atmosphere (Fu et al, 2015). It is worth noting that terrestrial VOCs from tundra and lakes at elevated concentrations were reported (Potosnak et al, 2013;Lindwall et al, 2016;Steinke et al, 2018). origin of this organic matter can be obtained by the FDOM analysis.…”
Section: Overview Of Aerosol Properties According To Different Air Mamentioning
confidence: 86%